ANALISIS RELEVANSI CITY BRANDING “BEAUTIFUL MALANG” MELALUI PENDEKATAN CITY BRAND INDEX DAN CITY BRAND PERSONALITY - Muhammad Mufli; Andriani Kusumawati (Jurnal Administrasi Bisnis, 2018)
The research investigated relevance of city branding of Beautiful Malang through city brand index and city brand personality approach. City brand index describes the competitive advantages of Malang which are reviewed from six aspects that are presence, potential, place, people, pulse and prerequisite. City brand personality identification of personal characteristics of Malang City which are viewed from the five dimensions that are sincerity, excitement, competence, sophistication, and ruggnedness.  The city brand index that, place get the high score. Brand personality of Malang City represent five dimension of city brand personality.  The City brand index aspects of Malang City that relevant to city branding “Beautiful Malang”  are place, people, pulse and potential, while indirect relevant  that are prerequisites and presence. The city brand personality scale of Malang City also shows that there are a few items the brand personality of Malang City has direct relevance to the "Beautiful Malang”. The other items have indirect relevance, can be become supporting into personality of Malang City. Based on the results of this research, it is suggested that the Government of Malang should to pay attention on aspects of potential and city personality into process of development or evaluation at City Branding “Beautiful Malang”. Keywords:  Malang City, Beautiful Malang, City Branding, City Brand Index, City Brand Personality ABSTRAK Penelitian ini membahas mengenai relevansi city branding “Beautiful Malang” melalui pendekatan city brand index dan city brand personality. City Brand index menjelaskan potensi unggulan Kota Malang yang ditinjau dari enam aspek yaitu presence, potential, place, people, pulse dan prerequisite. City brand personality mengidentfikasi karakteristik pribadi Kota Malang yang ditinjau dari lima dimensi ketulusan, kegembiraan, kecakapan, kecanggihan dan ketangguhan. Hasil city brand index menunjukkan bahwa aspek place mendapatkan penilaian tertinggi. Brand personality Kota Malang mewakili lima dimensi city brand personality. Aspek city brand index Kota Malang yang relevan dengan City branding “Beautiful Malang” adalah place, people, pulse dan potential, sedangkan yang tidak langsung adalah prerequisites dan presence. City brand personality scale Kota Malang juga menunjukkan bahwa terdapat beberapa  item yang membentuk brand personality Kota Malang memiliki relevansi langsung dengan city branding “Beautiful Malang”. Item yang lain tidak memiliki relevansi langsung, dapat menjadi pendukung dalam personality Kota Malang. Berdasarkan hasil penelitian ini, disarankan agar Pemerintah Kota Malang memperhatikan aspek potensi dan personality kota dalam proses pengembangan ataupun evaluasi pada city branding “Beautiful Malang”. Kata Kunci: Kota Malang, Beautiful Malang, City Branding, City Brand Index, City Brand Personality